Evaluate an Intermediary based Business Model in Location Based Services Market - Vijayan, Prijith (2010)
Location Based Services or LBS were predicted to be one of the few areas where users would be willing to pay a premium. According to Juniper forecast, the global MLBS market is forecasted to propel LBS market revenues through to over $12.7 billion by 2014. Despite the interesting market forecast, most of the LBS apps failed to generate reasonable revenue for startups. Paid and Advertising based business models have been in increasing popularity in the LBS market for over a decade. Due to high competition in the market, startups find it difficult to establish themselves using this unproven business models. Even though LBS apps are about people, of late there is an increasing focus on both the demand and supply side of the business. An intermediary based business model is becoming more popular in this industry. This report intends to throw some light on interesting intermediary business model adopted by some existing market players. The report discusses some major areas to focus in an intermediary business model that promotes Any to Any (A2A) transaction. Some of the major challenges while designing an intermediary business model like Network openness, building relationship, creating value and benefiting the contribution of the business partners and revenue model are also being discussed in this report.